Iron oxides in human spleen - Kopáni, Martin; Miglierini, Marcel; Lančok, Adriana; Dekan, Július; Čaplovicová, Mária; Jakubovský, Ján; Boča, Roman; Mrazova, Hedviga (Biometals, 2015)
Iron is an essential element for fundamental cell functions and a catalyst for chemical reactions. Three samples extracted from the human spleen were investigated by scanning (SEM) and transmission electron microscopy (TEM), Mössbauer spectrometry (MS), and SQUID magnetometry. The sample with diagnosis of hemosiderosis (H) differs from that referring to hereditary spherocytosis and the reference sample. SEM reveals iron-rich micrometer-sized aggregate of various structures-tiny fibrils in hereditary spherocytosis sample and no fibrils in hemochromatosis. Hematite and magnetite particles from 2 to 6 μm in TEM with diffraction in all samples were shown. The SQUID magnetometry shows different amount of diamagnetic, paramagnetic and ferrimagnetic structures in the tissues. The MS results indicate contribution of ferromagnetically split sextets for all investigated samples. Their occurrence indicates that at least part of the sample is magnetically ordered below the critical temperature. The iron accumulation process is different in hereditary spherocytosis and hemosiderosis. This fact may be the reason of different iron crystallization.
Keywords: Spherocytosis, Hereditary; pitva; Spectroscopy, Mossbauer; Ferrosoferric Oxide; krystalizace; železo; transmisní elektronová mikroskopie; Ferric Compounds; slezina; hemosideróza; Diffraction; Iron; železité sloučeniny; Crystallization; Humans; Magnetic properties; oxid železnato-železitý; Microscopy, Electron, Transmission; dědičná sférocytóza; Hemosiderosis; Spleen; spektroskopie Mossbauerova; lidé; Autopsy